Effect of Different Strengths of MS Media and BAP on Banana Plantlet Growth in Vitro - Nugrahani, Pangesti; Purnobasuki, Hery; Ansori, Arif Nur Muhammad; Anuchai, Jatuporn; Priyanto, Anugerah Dany (My University, 2024)
Banana tissue culture is commonly conducted using Murashiage and Skoog (MS) media supplemented with various types of growth regulators (PGRs). Cytokinin and Auxin are incorporated into MS media to promote shoot and root growth in banana explants. 6-benzyl amino purine (BAP), a form of cytokinin, plays a significant role in stimulating cell division and differentiation. This study aimed to assess the impact of BAP on various growth parameters, including shoot initiation, root initiation, leaf initiation, shoot and root length, plantlet weight, root number, leaf number, and shoot number. The study followed a completely randomized design with one factor, namely the composition of the planting medium, consisting of five treatments: full MS without BAP (MS0), ½ MS without BAP (½MS0), ¼ MS without BAP (¼ MS0), ½ MS supplemented with BAP at 3 mg L-1 (½ MSB), and ¼ MS supplemented with BAP at 3 mg L-1 (¼ MSB). The results revealed that the timing of shoot, root, and leaf initiation was not significantly altered by any of the treatments. However, shoot and root lengths were notably influenced by the treatment without BAP. Intriguingly, treatments without BAP consistently yielded superior growth outcomes, as evident from root growth and the number of leaves observed over 56 days after planting. The treatment of ¼ MS without BAP demonstrated the highest number of roots, with the ½ MS0 treatment displaying the highest number of leaves. In conclusion, utilizing MS growth media without BAP in banana tissue culture resulted in plantlets with robust growth and vigor, although the production of shoots was limited. The addition of 3 mgL-1 BAP at 1/2 MS gave the best number of shoots.
Keywords: 6-benzyl amino purine; Banana; MS media